Aggregation-induced negative differential resistance in graphene oxide quantum dots. Issue 31 (1st August 2021) - Sharma, Sonia; Cheng, Chieh-An; Santiago, Svette Reina Merden; Feria, Denice N.; Yuan, Chi-Tsu; Chang, Sheng-Hsiung; Lin, Tai-Yuan; Shen, Ji-Lin
Abstract : Negative differential resistance (NDR) devices have attracted considerable interest due to their potential applications in switches, memory devices, and analog-to-digital converters. Abstract : Negative differential resistance (NDR) devices have attracted considerable interest due to their potential applications in switches, memory devices, and analog-to-digital converters. Modulation of the NDR is an essential issue for the development of NDR-based devices. In this study, we successfully synthesized graphene oxide quantum dots (GOQDs) using graphene oxide, cysteine, and H2 O2 . The current–voltage characteristics of the GOQDs exhibit a clear NDR in the ambient environment at room temperature. A peak-to-valley ratio as high as 4.7 has been achieved under an applied voltage sweep from −6 to 6 V. The behavior of the NDR and its corresponding peak-to-valley ratio can be controlled by adjusting the range of applied voltages, air pressure, and relative humidity. Also, the NDR is sensitive to the the concentration of H2 O2 added in the synthesis. The charge carrier injection through the trapping states, induced by the GOQD aggregation, could be responsible for the NDR behavior in GOQDs.